Introducing STEM pedagogy in secondary school by means of Study and Research Path (SRP) - Gazzola Bascougnet, María Paz (2018)
This work shows the results of a research carried out in compulsory secondary school developing a Study and Research Path (SRP) on questions linked to the STEM approach. We present preliminary results of the SRPSTEM developed in five courses at secondary school with N=116 students. We describe the development and scope of the SRP by using its components as defined by the Anthropological Theory of Didactics (ATD). Furthermore, we present a short description of the Epistemological Model of Reference. We discuss some general results and conclusions concerning the connections between the STEM approach and the pedagogy of research and questioning the world.